LÖHNIG, M. – MOSZYŃSKA, A. (eds.) Reception of the ‘Limited Liability Company (GmbH)’ - Jan Beránek (Právněhistorické studie)
Book review on LÖHNIG, M. – MOSZYŃSKA, A. (eds.) Reception of the ‘Limited Liability Company (GmbH)’. Vídeň: Böhlau Verlag, 2024, 284 s.